Respiratory changes, hand fingers edema and yellow nails in a 94-year-old woman - Vitorino Modesto dos Santos; Christiane Aires Teixeira; Monique Chiovatto Montes Araújo; Manoel da Costa Gondim Neto; Iara Machado Motta; Melissa Gebrim Ribeiro (Italian Journal of Medicine, 2015)
A 94-year-old woman, with antecedent of chronic bronchitis, bronchiectasis, recurrent pneumonitis, arterial hypertension and chronic renal failure was admitted to control an episode of cardiac and respiratory insufficiency. Yellow nail changes and a tendency to pincer nails developed in her hand and toe fingers, preceded by longstanding course of respiratory diseases with pleural involvement. Laboratory tests detected moderate anemia and mildly elevated levels of urea and creatinine, thyroid function was normal. This case study is about yellow nail syndrome in the absence of ankle lymphedema, and affecting a woman of the oldest-old age group with renal failure.